Parenting Seminar on Positive Childrearing to Enhance Parents’ Understanding in Early Childhood Education - Tria Marini; Elsa Sriwahyuni; Ibnu Alrafi Anwar (Journal of Comunity Service in Early Childhood Education, 2026)
Background: Parenting plays a crucial role in shaping early childhood development, particularly in fostering children’s cognitive, emotional, and social growth. However, many parents still have limited understanding of positive childrearing practices, which may affect the quality of children’s development. This condition indicates the need for educational interventions that can improve parents’ knowledge and awareness of effective parenting strategies. Aims: This community service program aims to enhance parents’ understanding of positive childrearing practices in early childhood education through a structured parenting seminar. Methods: This program employed a Service Learning approach, integrating educational activities with direct community engagement. The implementation consisted of preparation, implementation, and evaluation stages. The seminar was conducted through lectures, discussions, and question-and-answer sessions. Data were collected using observation and participant response evaluation, and analyzed descriptively to assess the effectiveness of the program. Result: The results indicate that the parenting seminar successfully improved parents’ understanding of positive childrearing practices. Approximately 70% of participants demonstrated increased knowledge and awareness of appropriate parenting strategies, while more than 80% of invited participants attended the activity. Participants actively engaged in discussions and showed positive responses to the material presented, indicating high relevance and effectiveness of the program. Conclusion: The Service Learning-based parenting seminar is effective in enhancing parents’ understanding of positive childrearing practices. This program provides meaningful learning experiences and can serve as a practical and replicable model for community service in early childhood education contexts.